Organisationsgebundene pädagogische Professionalität Initiierter Wandel - Theoretisches Konstrukt - Narrative Methodologie - Interpretation - Schicke, Hildegard (Verlag Barbara Budrich, 2011)
Organization and profession - although they seem to contradict each other again and again in theory, in practice they are interlocked. For this reason, the author develops the theoretical construct of "organization-bound professionalism" in her work and relates it to the field of lifelong learning. The author proposes to grasp the social capacity to work in the pedagogical field in the social form of reflexively individualized professionalism and to focus on the structuring power of organization as a constitutional context of professionalism. It examined a four-year process of employee development in an educational institution for institutionalising competence-based forms of learning in continuing vocational education and training. Counselling and research were integrated, thus opening up the developmental process for a theory-generating reconstruction. Thus, it is assumed that organisation and professionalism are contingent within a socio-historical space of opportunity. Accordingly, plural concepts of what is understood by professionalism and organisation in theory and lived as the social reality of the educational institution are unfolded.